FEATURES OF ORGANIZATION OF EDUCATIONAL PROCESS ARE FOR HELP OF STOCHASTIC APPROACH IN THE EDUCATIONAL INFORMATION ENVIRONMENT FORMATION IN THE TECHNICAL HIGHER EDUCATIONAL INSTITUTIONS - Рахманов, В. О. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2016)
In the articles analyzed and the identified organization of educational process are certain by stochastic approach in the educational information environment formation in the technical higher educational institutions. The feature of this approach consists in that the conduct of process of studies in the future can be exactly foreseen, knowing his conduct in the past. Possibility to analyses the aggregate of the mastered knowledge not in relation to one theme of employments, but in relation to all of aggregates of the got knowledge by future engineers appears also. Results testify to the considerable improvements (worsening) of professional knowledge in future engineers. The uses of statistical methods of research in an educational process will give possibility to analyses the willingness of students to carry out effective professional activity on the basis of capture flexible knowledge, generalized abilities and skills